(untitled) (Jurnal Manajemen dan Kewirausahaan, 2012)
The role of Management Control System is very significant in improving the performance of companies that depend on the shape and culture of the organization. This study aims to determine the effect of interactions of organizational cultural with the process of management control systems, focussed at device controls and its mechanisms (such as evaluation and feedback system) to business unit performance in manufacturing and service industries in Jakarta. Data of the study was collected via a mail survey to business unit managers who heading a strategic business unit (SBU), profit center, or of divisional in manufacturing and services companies which listed in the Jakarta Stock Exchange. The statistic method used to test the hypotheses is a multiple regression multiplicative model. The results showed that corporate culture does not strengthen the relationship between attributes and mechanisms of SPM with business unit performance.